1987
DOI: 10.2307/3899592
|View full text |Cite
|
Sign up to set email alerts
|

Steer and Vegetation Response to Short Duration and Continuous Grazing

Abstract: Comparisons were made over a 4-year period between l-herd, 16pasture short duration grazing (SDG) and continuous grazing (CC) on the Texas High Plains. Animal performance, vegetation response, and diet quality were evaluated. Stocking rate on SDG was equal to that on CC the fhst year (13.3 ha/AU), double that on CG in the second year, and 1.5 times that on CG the third and fourth years. Average daily gain (ADG) of steers was the same (0.33 kg/day) between SDG and CG the first year. When stocking was doubled on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 2 publications
3
18
0
Order By: Relevance
“…Continuous and rotational grazing systems differ little in terms of their effects on range condition in the short-term (Denny et al 1977, Pitts and Bryant 1987, Hart et al 1988, O'Reagain and Turner 1992. We hypothesize higher range condition in rotational system pastures will result in the long-term from increased vigor of desirable plants due to fewer defoliations during the grazing season.…”
Section: Discussionmentioning
confidence: 82%
“…Continuous and rotational grazing systems differ little in terms of their effects on range condition in the short-term (Denny et al 1977, Pitts and Bryant 1987, Hart et al 1988, O'Reagain and Turner 1992. We hypothesize higher range condition in rotational system pastures will result in the long-term from increased vigor of desirable plants due to fewer defoliations during the grazing season.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have shown short-duration grazing to be similar to continuous grazing in effects on plant succession and range condition if stocking rates were the same (Pitts and Bryant 1987, White et al 1991, Manley et al 1997, Gillen et al 1998. In a south Texas study, it was found that progressively increasing the stocking rate under short-duration grazing up 2.5 times the rate recommended by Merrill (1954) caused the frequency and composition of mid-grasses to decline but shortgrasses were not affected (Ralphs et al 1990).…”
Section: Plant Succession and Range Conditionmentioning
confidence: 99%
“…Four studies have shown short-duration grazing has lowered individual livestock productivity compared to continuous or season-long grazing (Parker et al 1987, Anderson 1988, Heitschmidt et al 1990, McCollum et al 1999. Another 5 studies showed no difference between short-duration and continuous grazing (Jung et al 1985, Pitts and Bryant 1987, Olson and Malechek 1988, Taylor et al 1993, Manley et al 1997) while 1 study showed short-duration grazing increased livestock productivity (Daugherty et al 1982). A careful analysis of these 10 studies indicates small or no difference in livestock productivity between short-duration and continuous grazing if stocking rates are equal with one exception.…”
Section: Livestock Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, herding is impractical if not impossible in large cattle herds (Hunt et al 2007). Even though herding can facilitate appropriate use, man's fallibility in consistently making correct choices has not always shown herding to improve livestock distribution (Pitts and Bryant 1987) or positively benefit the amount of forage and its nutritive value; therefore, VF will only be as good as those who operate this virtual herding system.…”
Section: Stocking Strategiesmentioning
confidence: 99%